Desarrollo de la lateralidad a través de las rondas infantiles - Pullupaxi Alvarez, Liliana Elizabeth (2016)
The purpose of the research that is presents is to give to know both to teachers as to students the importance that have them round children’s for the development of the laterality of there this present research is based in the objective general "Diagnose as them rounds children’s affect in the development of the laterality of children of second years of Education General Basic of Juan Abel Echeverria Unit in the year school 2015-2016" basic general education is to form boys and girls for their future school stage, so was this research on children’s rounds for the development laterality. This work is the answer to the problem of theoretical content and conceptual allow substantiate the contents of laterality and children’s rounds in educational processes. Rounds children’s for the development of laterality is transcendental for the processes of teaching and learning processes of infants since this helps their emotional, psychological training cognitive, socio-emotional, motor and playful, in this way the research work consists of the study of many elements that allow us to evidence from the theoretical point of view to take it to the practice of publicizing the importance of the because teachers must be with children and girls rounds children’s as a way methodology to develop laterality. Within this research project is studied on the importance, objectives, types, definitions by authors in if the Foundation theoretical and scientific of them rounds children’s, as well as also on the laterality.